A study on the mixture repairing effect of biochar and nano iron oxide on toxicity of Cd toward muskmelon. (November 2020) - Zou, Zhengkang; Wang, Yunqiang; Huang, Jiali; Lei, Zhen; Wan, Fengting; Dai, Zhaoyi; Yi, Licong; Li, Junli
Abstract: Soil contamination with cadmium (Cd) has become a serious problem, adversely affecting food safety and human health. Effective methods are urgently needed to alleviate toxicity of Cd in plants. In this study, a nine-week continuous pot experiments was conducted to explore the effectiveness of the different nano iron oxide (α-Fe2 O3, γ-Fe2 O3, Fe3 O4 ) alone and combined with biochar in muskmelon grown on a Cd-contaminated soil. The antioxidant system, chlorophyll, soluble protein, other physiological indexes of muskmelon leaves and the distribution of Cd in matrix soil, leaves and fruit were detected. The results showed that Cd was readily absorbed by plants and caused oxidative stress on plants, while biochar, α-Fe2 O3 nanoparticles (NPs) and their mixture group (BFe1 group) could significantly improve it. Specifically, the three treatments reduced the Cd content of the fruit by 19.51–78.86%, reduced the Cd content of leaves by 15.44–36.23% and 22.36–31.77% in weeks 3 and 5, respectively. For the activity of enzymes, three treatments decreased superoxide dismutase (SOD) activity and catalase (CAT) activity by 3.41–38.57% and 24.27–30.33% in week 7, respectively. So BFe1 group application immobilized Cd in soil and reduced Cd partitioning in the aboveground tissues. Overall the combination of biochar and α-Fe2 O3 NPs can alleviate Cd toxicity in muskmelon and can protect human beings from Cd exposure. Graphical abstract: Image 1 Highlights: Cd content in fruits of all treated groups were significantly reduced. Compared to γ-Fe2 O3 and Fe3 O4, biochar and α-Fe2 O3 NPs are more suitable for alleviating cadmium toxicity. Biochar combined with α-Fe2 O3 NPs could alleviated the oxidative damage of melon produced by Cd 2+ . Abstract : Capsule: Biochar treatment and α-Fe2 O3 NPs treatment could significantly alleviate Cd toxicity toward muskmelon and combinations worked better.